A reactive probe for Co2+ ion detection based on a catalytic decomposition process and its fluorescence imaging in living cells. (15th July 2020) - Ji, Liguo; Yang, Chengliang; Li, Huijie; Yang, Nan; Fu, Yutian; Yang, Linlin; Wang, Qingzhi; He, Guangjie
Abstract: A novel reactive fluorescent probe for cobalt ions was prepared based on integration of thiourea functional groups, coumarin, and naphthalimide fluorophores. There was no fluorescence observed for the probe itself, however, in the presence of cobalt ions, catalytic decomposition occurred for the probe and coumarin molecular fragments were produced that emitted blue fluorescence. This enabled the probe to be used as a 'turn on' reagent for detection of cobalt ions. Under physiological pH conditions and in appropriate solvent systems, an obvious fluorescence enhancement for cobalt ions was observed in selective experiments. Competition experiments indicated that cobalt ions could still induce fluorescence enhancement in the presence of other metal ions. Sensitivity experiments showed that the detection limit for cobalt ions was 6.0 nM. Dynamics research demonstrated that the catalytic process was a pseudo‐first‐order reaction and the reaction constant (kobs ) was calculated to be 1.49 × 10 −2 min −1 . In addition, the mechanism of catalytic decomposition could be demonstrated using electrospray ionization mass spectrometry and thin layer chromatography experiments. Cell fluorescence imaging experiments demonstrated that the probe could be used to detect cobalt ions in living HeLa cells. Abstract : A novel reactive fluorescent probe for detection of cobalt ions was produced, which exhibited high selectivity and sensitivity for Co2+ ions as a "turn on" fluorescent probe. The probable mechanism might involve a process of catalytic decomposition of the probe induced by cobalt ions. The cell fluorescence imaging experiment demonstrated that it could be used in living Hela cells.